Pengaruh pemberian pendidikan kesehatan terhadap sikap mengkonsumsi tablet fe pada ibu hamil - Indriyani Makmun; Ismarwati Ismarwati (Universitas Aisyiyah Yogyakarta, 2016)
The high prevalence of anemia can be influenced by the behavior of wayward mother taking iron suplementation. The research objective determine the impact of health education on attitude of consuming iron suplementation. Designstudy is Quasi Experiment with pre-test post-test non-equivalent control group design.The sample was 58 with consecutive sampling technique.Analysis used Mann-Whitney and multiple regression for multivariable analysis. The results showed after intervention, then there is increased behavior with p= 0.005 (p0.05). External variables is education with p 0.05. The conclusions are the effect of health education on attitude of consuming iron suplementation anemia in pregnant women.